Multiple time scale redundancy control for QoS-sensitive transport of real-time traffic - Tsunyi Tuan; Kihong Park (Proceedings IEEE INFOCOM 2000. Conference on Computer Communications. Nineteenth Annual Joint Conference of the IEEE Computer and Communications Societies (Cat. No.00CH37064), 2000)
End-to-end QoS control over best-effort and differentiated service networks which exhibit variability in their exported service properties looms as an important challenge. In previous work, we have shown how packet-level adaptive FEC can be used in dynamic networks to facilitate invariant user-specified QoS in an end-to-end manner. This paper addresses two important problems-self-similar burstiness and performance degradation of reactive controls subject to long feedback loops-complementing the stability/optimality considerations studied earlier. First, for adaptive redundancy control to be effective, its susceptibility to correlated packet drops and queueing delays stemming from self-similar burstiness must be fortified. Second, to preserve FEC's viability over ARQ when transporting real-time traffic in WAN, preactivity must be injected to offset the performance degradation of reactive feedback controls when subject to long RTT. In this paper, we use the recently advanced multiple-time-scale congestion control framework-first investigated in the throughput maximization context-to endow adaptive redundancy control with both selective protection against self-similar burstiness as well as preactivity to feedback redundancy control. We analyze, implement, and benchmark our protocol-AFEC-MT-in the context of transporting periodic real-time traffic, in particular, MPEG video.